2002
DOI: 10.1073/pnas.062536499
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale surface chemistry

Abstract: We report evidence in several experiments for nanometer-size effects in surface chemistry. The evidence concerns bimetallic systems, monolayer films of Pt or Pd on W(111) surfaces. Pyramidal facets with {211} faces are formed on annealing on physical monolayer of Pt, Pd on a W(111) substrate, and facet sizes increase with annealing temperature. We used synchrotron radiation-based soft x-ray photoemission to show that monolayer films of Pt, Pd, on W ''float'' on the outer surface, whereas multilayer films form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
(35 reference statements)
0
35
0
Order By: Relevance
“…The presence of co-adsorbed O 2 appears to have opposite effects on the computed CO adsorption energies on supported Pt 3 and Au 3 : it reduces that of CO on Pt 3 /TiO 2 by ∼0.3 eV and increases E CO ads on Au 3 /TiO 2 by approximately the same amount (Table IV) in the absence (Table III) and presence (Table IV) …”
Section: Co Adsorption On Ptmentioning
confidence: 90%
See 3 more Smart Citations
“…The presence of co-adsorbed O 2 appears to have opposite effects on the computed CO adsorption energies on supported Pt 3 and Au 3 : it reduces that of CO on Pt 3 /TiO 2 by ∼0.3 eV and increases E CO ads on Au 3 /TiO 2 by approximately the same amount (Table IV) in the absence (Table III) and presence (Table IV) …”
Section: Co Adsorption On Ptmentioning
confidence: 90%
“…On stoichiometric TiO 2 , two Pt atoms of the trimer bind with two neighboring O 2c at distance 2.056 Å and two Ti 5c at distance 2.664 Å. Consequently, the Pt-Pt bond parallel to the surface is slightly longer (2.516 Å) than the other two Pt-Pt bonds (2.508 Å) pointing away from Similarly Figure 4. For Pt 3 , we can see a large number of metal states in the TiO 2 band gap, which makes the overall band gap nearly vanishing. On the stoichiometric surface (Figure 4(a)), no Ti occupied state is present near the Fermi level (E F ), as expected.…”
Section: Supported Pt 3 and Au 3 Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that atomically rough, high energy surfaces may be morphologically unstable during reaction conditions. 9 In contrast to the closed packed faces, the high-index surfaces may undergo massive structural rearrangements ͑e.g., faceting͒ when covered by a metallic film. It is also shown that film growth mode on nanofaceted surface may be very different from a growth mode on the flat substrate.…”
Section: Introductionmentioning
confidence: 99%